Diseño de un plan de negocios para la exportación de papaya hacia la Florida - Estados Unidos (2019)
In the present work a business plan was developed for the export of papaya to Florida-United States, for this it was necessary to carry out an analysis of the agriculture sector in Colombia, which showed that it has had a good dynamic throughout the years. Recent years despite the fact that papaya growth has not been the best; this becomes an opportunity to cover with that offer. Another important aspect for the development of the project was to identify the generalities of the papaya and the subsequent technical analysis on the patterns of its cultivation; those indispensable variables were identified so that the desired results are obtained.